2002
DOI: 10.1590/s1519-69842002000500004
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of fish species richness in rivers of the central region of Argentina

Abstract: We analyzed the variation of fish species richness and trophic structure along an upstream-downstream gradient and identified the factors associated with the pattern observed. The fish community composition varied along a headwater-downstream gradient. Species richness and trophic structure decreased significantly with increasing altitude and increased with stream order and distance from source. Headwater communities showed a simple structure. Oncorhynchus mykiss was the only fish captured or noticeably domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
35
0
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 17 publications
8
35
0
8
Order By: Relevance
“…The altitude coefficients obtained for the four species showed a negative influence of this parameter over the analyzed species distribution. With higher altitudes the smaller habitat heterogeneity and the dynamic instability determine conditions in which few species are able to tolerate (Bistoni & Hued, 2002). In rivers of central Argentina, distribution of the species according to an altitudinal gradient was also observed: Pimelodus albicans reaches altitudes between 600 and 800 m; Prochilodus platensis (= P. lineatus), between 400 and 600 m; and Salminus maxillosus (= S. brasiliensis), between 200 and 400 m (Bistoni & Hued, 2002).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The altitude coefficients obtained for the four species showed a negative influence of this parameter over the analyzed species distribution. With higher altitudes the smaller habitat heterogeneity and the dynamic instability determine conditions in which few species are able to tolerate (Bistoni & Hued, 2002). In rivers of central Argentina, distribution of the species according to an altitudinal gradient was also observed: Pimelodus albicans reaches altitudes between 600 and 800 m; Prochilodus platensis (= P. lineatus), between 400 and 600 m; and Salminus maxillosus (= S. brasiliensis), between 200 and 400 m (Bistoni & Hued, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…With higher altitudes the smaller habitat heterogeneity and the dynamic instability determine conditions in which few species are able to tolerate (Bistoni & Hued, 2002). In rivers of central Argentina, distribution of the species according to an altitudinal gradient was also observed: Pimelodus albicans reaches altitudes between 600 and 800 m; Prochilodus platensis (= P. lineatus), between 400 and 600 m; and Salminus maxillosus (= S. brasiliensis), between 200 and 400 m (Bistoni & Hued, 2002). In the present study, we observed that Pimelodus pintado (680 m) and Prochilodus lineatus (297 m) occurred in lower altitudes than their co-generic species from Argentina, although S. brasiliensis (292 m) presented the same altitudinal pattern of S. maxillosus (= S. brasiliensis).…”
Section: Discussionmentioning
confidence: 99%
“…Seguindo tal tendência os três córregos analisados apresentaram uma baixa riqueza específica, com elevada representatividade numérica de apenas três espécies (P. reticulata, H. ancistroides e R. quelen). Em termos gerais, a riqueza, diversidade e eqüitabilidade aumentaram em direção aos segmentos inferiores (jusante), coincidindo com resultados encontrados para ambientes naturais (ABES & AGOSTINHO 2001, BISTONI & HUED 2002. Porém, a alta representatividade de P. reticulata, e a baixa densidade de espécies nativas características dos ambientes amostrados destacaram a influência do intenso aporte de poluentes nas cabeceiras sobre toda a extensão dos córregos.…”
Section: Discussionunclassified
“…O índice de diversidade Beta-2, da mesma forma, evidenciou aumento da heterogeneidade ambiental e da ictiofauna em direção à jusante, corroborando com estudos prévios para ambientes naturais (PALLER 1994, BISTONI & HUED 2002. Entretanto, a manutenção da alta representatividade de espécies tolerantes à poluição e a não substituição destas por espécies características dos segmentos inferiores evidenciou, embora não de maneira exclusiva, a manutenção de estresses presentes nas porções de cabeceira sobre toda a extensão dos córregos.…”
Section: Discussionunclassified
“…However, knowledge of both salmonid and native species composition in high altitude Córdoba rivers is still fragmentary, being most of fish records supported by surveys in middle altitude streams (1000 to 1500 m). For example Bistoni & Hued (2002) analyzed species richness with regard to height in the Primero, Segundo, Tercero and Cuarto river basins concluding that such areas represent "trout zones" due to the fact that only few native species mostly belonging the Loricariidae and Trichomycteridae families were found. In turn, Pampa de Achala streams are located in high altitude areas (1500 to 2200 m) where Haro & Bistoni (1996) highlighted the importance of salmonid species as the basis of an important recreational fishery.…”
Section: Introductionmentioning
confidence: 99%